Strategies For Managing Disruptive Behaviours Among Public Secondary Schools’ Students in Classrooms in Kogi East Education Zone Nigeria - Shaibu Leonard; Mohammed Sani Haruna; Ogwu Hannah Inikpi; Ukpoju Bartholemew Ojochenemi (Center of Research and Innovation Strengthen LP2M UNM, 2023)
The study investigated strategies for managing disruptive behaviours among public secondary school students in classrooms in Kogi East Education Zone. The purpose of the study was to find out the causative factors responsible for students’ classroom disruptive behaviours and strategies to be adopted by public secondary school teachers in the management of students’ classroom disruptive behaviours. Two research questions guided the study. A descriptive survey design was adopted. The population of the study consisted of 2434 teaching staff from 208 secondary schools in the Kogi East education zone. A sample of 400 teachers representing 16% was purposively selected for the study. The Disruptive Behaviour Management Questionnaire (DBMQ) was used as an instrument for data collection. Mean and standard deviation was used to answer the research questions that guided the study with a benchmark of 2.50 for acceptance and rejection. It was revealed from the analysis that (1) hereditary factors, visual disability, mental disability, excessive intelligent quotient in an individual student, exposure of students to the use of computers, television, radios, internet, mobile phones and frustration resulting from emotional to be the causative factors responsible for students’ classroom disruptive behaviours in Kogi East Education Zone. (2) Finding the cause, inducing the desirable behaviour, eliminating the undesired behaviour, systematic desensitization, ignoring strategy, dealing directly with persistent behaviours and monitoring techniques to be strategies for managing students’ disruptive behaviours in the classroom in Kogi East Education Zone. Some recommendations were also made.